Model and simulations of multipath bridge routing for inter-swarm UAV communications in EMANE/CORE. (4th May 2022) - Chu, Zhe; Hu, Fei; Bentley, Elizabeth Serena; Kumar, Sunil
ABSTRACT: The unmanned aerial vehicle (UAV) network is a special type of mobile ad hoc network (MANET). 1 There are two types of UAV swarm communications: Communications within a swarm (i.e. intra-swarm) and communication between different swarms (i.e. inter-swarm). This paper proposes the concept of bridge routing to establish the route(s) for efficient inter-swarm communications. The bridge routing scheme is a progressive process with two functions: UAV formation control and data transmissions. Based on the bridge routing topology, we have implemented the multipath user datagram protocol (MP-UDP), as a sub-layer between the transport and application layers. Compared with the multipath transmission control protocol (MP-TCP), MP-UDP is more suitable to the dynamic network topologies, since it does not use the high-overhead sliding window control. We have used the emulator tools, the Extendable Mobile Ad -hoc Network Emulator (EMANE) and Common Open Research Emulator (CORE) to implement and study the QoS performance of MP-UDP and bridge routing in UAV swarm networks. Our results demonstrate the improved throughput performance for inter-swarm communications. Approved for Public Release; distribution unlimited 88ABW-2020-2122 on 13 July 2020. Other requests shall be referred to AFRL/RIT 525 Brooks Rd Rome, NY 13, 441